Investigation of suicide cases due to agricultural drugs - Dulger, H.E.; Ege, B.; Erturk, S.; Yemiscigil, A. (My University, 1994)
Results of autopsy and toxicologic analysis and the records of 154 suicide cases that used agricultural drugs which autopsies were performed by Forensic Medicine Council Izmir Group Chairmanship Morque Specialization Office during 1980-1990 were evaluated. Cases were investigated according to age, sex, distribution in months, substance used and the presence of suspected substance found at the scene. It was detected that drinking of agricultural drugs were at the first order between the suicide methods, organic phosphorous compounds were more used rather than other compounds.
TARIMSAL ILACLAR ILE INTIHAR OLGULARININ INCELENMESI
Keywords: Pesticides; Suicides